UJI HAYATI LARVA NYAMUK Aedes aegypti TERHADAP LARVASIDA TEMEPHOS 1% (ABATE 1 SG) DENGAN BERBAGAI KONSENTRASI DI KELURAHAN SESETAN DENPASAR SELATAN - Amelia, Irene; Sudarmaja, I Made; Ariwati, Ni Luh (E-Jurnal Medika Udayana, 2023)
Temephos 1% (Abate 1 SG) larvicide has long been used to control Aedes aegypti mosquito as dengue vectors. The use of larvicide for a long time and in excessive amounts can cause resistance. The aims of this research are to determine the effectiveness of various concentrations of temephos 1% (Abate 1 SG) and to determine the resistance status of Aedes aegypti larvae in Sesetan Village South Denpasar. This study was experimental post test only with control group design. Aedes aegypti larvae instar III / IV rearing results from larvae obtained in Sesetan Village South Denpasar were tested with temephos concentrations of 0.003 mg/l; 0.006 mg/l; 0.012 mg/l; 0.024 mg/l; and 0.05 mg/l. The number of deaths was counted after 24 hours and was repeated 5 times. Data analysis was performed using the Kruskal Wallis and Mann Whitney tests and obtained p value < 0.05 for Kruskal Wallis, which means that there is a difference in mortality of Aedes aegypti larvae. According to WHO’s diagnosis dose (0.012 mg/l), Aedes aegypti larvae in Sesetan Village South Denpasar is still sensitive to temephos with 100% mortality. Lethal Concentration (LC) 50 and 99 is 0.003 mg/l and 0.011 mg/l. It can be concluded that Aedes aegypti larvae in Sesetan Village South Denpasar are not resistant to temephos 1% (Abate 1 SG) larvicide, so that the larvicide is still effective for use.